2023
DOI: 10.3389/fpsyg.2023.1093446
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of resilience on mental health literacy and positive coping style among Chinese empty nesters: A cross-sectional study

Abstract: ObjectivesEmpty nesters in China have limited mental health literacy (MHL), which may lead to poorer health outcomes. Studies demonstrate that MHL is associated with both resilience and positive coping style. However, the potential mechanism of MHL, resilience and positive coping style remain unclear. Therefore, the study aims to investigate the possible mediating role of resilience in the relationship between MHL and positive coping style.MethodIn this cross-sectional study, a total of 363 empty nesters from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“… 3 , 37 Conversely, individuals who are prone to utilizing negative coping strategies tend to have lower levels of psychological resilience, as negative coping styles negatively predict psychological resilience. 37 , 38 However, there has been no exploration of the relationship between negative coping styles and positive coping styles in terms of psychological resilience in earlier studies. Moreover, there is a lack of follow-up studies conducted over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 37 Conversely, individuals who are prone to utilizing negative coping strategies tend to have lower levels of psychological resilience, as negative coping styles negatively predict psychological resilience. 37 , 38 However, there has been no exploration of the relationship between negative coping styles and positive coping styles in terms of psychological resilience in earlier studies. Moreover, there is a lack of follow-up studies conducted over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study suggest that better knowledge regarding mental health disorders may be beneficial for one's resilience. Recently, studies conducted among Chinese adolescents, college students and older Chinese individuals revealed that MHL was positively associated with resilience (Song et al, 2023;Zhang et al, 2023aZhang et al, , 2023b. MHL is associated with self-management and self-efficacy as well as with positive coping styles (Song et al, 2023;Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies conducted among Chinese adolescents, college students and older Chinese individuals revealed that MHL was positively associated with resilience (Song et al, 2023;Zhang et al, 2023aZhang et al, , 2023b. MHL is associated with self-management and self-efficacy as well as with positive coping styles (Song et al, 2023;Zheng et al, 2018). It appears that individuals with more knowledge may feel better equipped to take proper care of themselves, thus potentially enhancing their resilience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations